Role of protein synthesis and of fatty acid metabolism in the longer-term regulation of pyruvate dehydrogenase kinase - Priestman, D; Mistry, S; Halsall, A; al., E (Portland Press, 1994)
Antibodies were raised in rabbits to free rat liver pyruvate dehydrogenase (PDH) kinase alpha-chain and shown to react with PDH kinase alpha-chain in rat heart and liver PDH complexes, in purified pig heart PDH complex and in bovine kidney dihydrolipoamide acetyltransferase-protein X-PDH kinase subcomplex. E.l.i.s.a for PDHE1 (pyruvate dehydrogenase) and PDH kinase have been developed and applied to assays of these proteins in extracts of rat liver and rat heart mitochondria; the measured immunoreactivities for PDHE1 (heart > liver) and for PDH kinase alpha-chain (liver > heart) paralleled known differences in PDH complex and PDH kinase activities respectively. The results of e.l.i.s.a of PDH kinase alpha-chain in extracts of rat liver mitochondria showed that the effects of starvation to increase PDH kinase activity in vivo, and the effects of dibutyryl cyclic AMP or palmitate to increase PDH kinase activity in hepatocytes cultured in vitro, are due largely (> 90%) to an increase in the specific activity of PDH kinase. The effect, in cultured hepatocytes, of dibutyryl cyclic AMP to increase PDH kinase activity was blocked by cycloheximide; the effect of palmitate was blocked by an inhibitor of carnitine palmitoyltransferase I (Etomoxir), but not by cycloheximide.